Finite Element Analysis of Newly Developed Endosseous Root-Form Dental Implant Utilizing Biodegradable Magnesium Alloy - Han, Hyung-Seop; Kim, Yu-Chan; Seok, Hyun-Kwang (PROCEEDINGS OF 2016 7TH INTERNATIONAL CONFERENCE ON MECHANICAL AND AEROSPACE ENGINEERING (ICMAE), 2016)
The purpose of this study was to investigate the fatigue life of an endosseous root-form dental implant using finite element analysis. A conventional Brnemark dental implant system was redesigned to utilize the biocompatible, lightweight magnesium alloy which promotes bone growth. ANSYS Workbench 11.0 was used to generate a three-dimensional mesh of a model created with the actual size specifications. Regulations and schematic of test set-up from ISO 14801 - "Fatigue test for endosseous dental implants" were strictly followed to simulate the fatigue test. To validate the credibility of calculated fatigue life, actual prototypes were built with the design specifications and tested using Material Test System 810. Result of finite element analysis displayed a close approximation of experimental fatigue behavior both displaying that the proposed implant would achieve a fatigue limit of 5 x 106 cycle suggested by the ISO at 150 N. The main advantage of performed computer simulations is that it is fast, efficient and cheap. A comparison of the calculated fatigue life with experimental fatigue life data displayed the accuracy and reliability of the computer simulation method.